Profile of dog bite cases attending the outpatient department of an urban health training centre in Bangalore city, India - C., Karthik; P. G., Viswanatha; Shobha, .; T. S., Ranganath; P., Sushmitha (International Journal Of Community Medicine And Public Health, 2016)
Background: Human rabies, a viral zoonotic disease, primarily involving the central nervous system is transmitted by the bites or licks of canines especially dogs. It almost always culminates in death demanding prompt intervention in the form of vaccines and immunoglobulins. Despite availability of such preventive measures, compliance at times is not satisfactory. This study was conducted to know the profile of dog bite cases and estimate the compliance of the same attending the outpatient department (OPD) in an Urban Health Training Center (UHTC) in the field practice area of Bangalore Medical College and Research Institute (BMCRI). Methods: It is a retrospective record based study conducted from April 2013 to March 2014 in the UHTC in the field practice area of BMCRI, among all the dog bites cases who attended the OPD. Results: Of the total 637 cases, 461(72.4%) were males and 176 (27.6%) were females. Most of the cases 192 (30.14%) were less than 15 years of age. Of the 637 cases, 119 were of category 1 bites and the remaining 518 which included 132 category 2 cases and 386 category 3 cases actually required vaccination. A total of 218 cases had taken all the 4 doses of intradermal vaccination and the remaining 351 were only partially immunized with 138 cases receiving the 1st dose, 87 the 2nd and 126 the 3rd dose. Conclusions: Men are more affected as they are more out in the open to earn a livelihood for their family.